Smart Aquaculture in Internet of Things-based Catfish Farming - Kurniawan Budi Kusnanto; Aris Nasuha (Journal of Robotics, Automation, and Electronics Engineering, 2023)
The primary objective of developing the project titled "Smart Aquaculture in Internet of Things-based Catfish Farming" is to create a specialized tool for catfish farming that facilitates automated monitoring and control of water quality, eliminating the need for manual intervention at the aquaculture pond. The collected data is made accessible through a web monitoring system. The tool aims to mitigate catfish mortality risks, enhance yield, and streamline the cultivation process. The development process of this tool encompasses several stages, which are as follows: (1) Requirements Analysis, involving the identification of necessary tools and materials for the project; (2) Implementation, encompassing the design and fabrication of the tool, outlining the circuit scheme, and detailing the step-by-step manufacturing process; (3) Testing, describing the procedures and results of evaluating the tool's performance. The monitoring system employs PH- 4502C sensors, DS18B20 temperature sensor, and HC-SR04 level sensor, all controlled by ESP32 DevKit. Comparative analysis against standard measuring instruments demonstrates an average error percentage of 1.64% for pH, 0.88% for temperature, and 0.70% for water level measurements. Additionally, the data transmission test reveals a delay of 19.16 seconds, while the actuator response test, based on sensor readings, successfully operates within the system's intended parameters.